Governing Migration for Development from the Global Souths Challenges and Opportunities - Degila, Dêlidji Eric; Valle, Valeria Marina (Brill, 2022)
The 14th thematic volume of International Development Policy provides perspectives through case studies from the global Souths focusing on the challenges and opportunities of governing migration on the subnational, national, regional and international levels. Bringing together some thirty authors from Africa, Latin America and Asia, the book explores existing and new policies and frameworks in terms of their successes and best practices, and looks at them through the lens of additional challenges, such as those brought on by the COVID-19 pandemic, the rise of nationalisms and an increase in xenophobia. The chapters also take the '5 Ps' approach to sustainable development (people, planet, prosperity, peace and partnerships) and assess how migration policies serve sustainable development in a rapidly evolving context. Contributors are Yousra Abourabi, Gabriela Agosto, Belkis Aracena, Andrea Fernández Benítez, Macarena Chepo, Amanda Coffie, Jonathan Crush, María del Consuelo Dávila Pérez, Dêlidji Eric Degila, Jenny Lind Elmaco, René Leyva Flores, Luisa Feline Freier, Silvia Núñez García, Marcela Pezoa González, Binod Khadria, Ariel González Levaggi, Wei Li, Meixin Liu, Ling Ma, Ratnam Mishra, Daniel Naujoks, Claudia Padilla, Karol Rojas, Fabiana Rubinstein, Yining Tan, Narender Thakur, Gerasimos Tsourapas, Valeria Marina Valle and Jossette Iribarne Wiff.